Analysis of Digital Data for Records Monitoring the Quantity of Drinking Water Produced in Ibb City for the Period Between (2019-2023) (مجلة جامعة سرت للعلوم الانسانية, 2024)
This study aims to extract the numerical and relative variation of the wells of the Local Corporation for Water and Sanitation, Ibb City Branch, and to indicate the amount of variation in the values of the amount of water produced from it, as well as the analysis and interpretation of the numerical data of the records of monitoring the quantity of water produced in Ibb city during the period between (2019-2023), using the historical, descriptive, and analytical approach, as the number of non-operating corporation wells reached (14) wells, representing (32%) of the total (44) wells, and the largest value was monitored by the amount of water produced from The wells operating in the year (2023), as it amounted to (7,120,141) m3/year, i.e.: (22.8%) of the total amount of water produced during the period between (2019-2023), amounting to (29,773,335) m3/year, while the largest value of the average daily per capita share of produced water was recorded in the year (2023), as it amounted to (34) liters / day per person, with an increase of (132%) over the year (2019).
Keywords: Groundwater Wells; Water Produced; Supply; Ibb City; Yemen